A Comparative Study of Residents’ Attitudes Toward Urban Greening in Matsubara and Honjo, Tokyo - Sang Beijia; Shimizu Ikuro (E3S Web of Conferences, 2025)
This study focuses on two representative districts in Tokyo—Matsubara and Honjo—and conducts a cross-sectional questionnaire survey (N = 202) to systematically analyze the influence of social background and housing conditions on residents’ greening behavior. It also explores residents’ motivations, obstacles, policy awareness, and participation in greening activities. The results show that women, households with more family members, and long-term residents are more likely to engage in greening. In terms of housing conditions, those living in owned houses, detached houses, residences with gardens, and larger homes exhibit significantly higher participation rates in greening than tenants or apartment dwellers. The data further reveal that while the primary motivations for greening in both areas are beautifying the environment and personal interest, the perceived obstacles differ: lack of time is the main barrier in Matsubara, whereas limited space is the primary issue in Honjo. Additionally, residents in Matsubara demonstrate higher levels of policy awareness and participation in greening activities, indicating that the overall greening environment of a district may positively influence individual behavior. Based on these findings, this study suggests that urban greening policies should incorporate differentiated support tailored to residents’ social attributes and housing characteristics, thereby promoting equity and sustainability in urban greening initiatives.